PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF PADA MATERI MAD KELAS IX DI MTS DARUL ULUM PALANGKA RAYA - Misbah Misbah; Jasiah Jasiah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to develop the use of interactive multimedia-based media to improve student understanding and improve the concentration of learning of class IX students at MTS Darul Ulum Palangka Raya in the learning process of Mad material. In this study using a research model, namely the ADDIE model with data collection techniques in this study, namely interviews, observations, documentation and questionnaires. The questionnaire was given to media experts, material experts, Al-Quran Hadith teachers and students. The data collected were analyzed descriptively quantitatively. The results of this study stated that at the Analysis stage the researcher conducted a material analysis. The second stage is design, designing the initial draft of the media. The third stage of development, the resulting product is in the form of a video with the results of the validation of the material expert obtained with a validity result of 79% with good criteria and the results of the validation of the media expert obtained with a result of 82% with very feasible criteria. The teacher's response received an assessment of 100% in the very good category and the trial of 24 students got a score of 62% in the sufficient category. So it can be said that students feel happy and interested. The fourth stage is implementation, at this stage the researcher tests the media. Finally, there is evaluation, at this stage the researcher analyzes the impact of using the media. This study can conclude that the use of interactive multimedia-based media will help improve the concentration and understanding of students at Mts Darul Ulum Palangka Raya.